Le système d’orientation professionnelle des lycéens aux États-Unis d’Amérique - Yuliia Zahrebniuk (Éducation et Socialisation)
The aim of the article is to examine the system of career guidance of high school students in the United States of America. The methodology is based on the analyses of the process of career guidance work in the USA, the structure of secondary education in the USA, the role of career counselors, the principles of professiography, three stages in the work of counselors in the Unites States of America. In order to analyse the general system of professional self-determination of students in secondary schools in the United States, it is considered the structure of secondary education in this country. The 10 participants in the action research were career counselors from the USA.